Mobility experiences of adult lower limb orthosis users: a focus group study. Issue 25 (4th December 2022) - Balkman, Geoffrey S.; Hafner, Brian J.; Rosen, Rachael E.; Morgan, Sara J.
Abstract: Purpose: People with lower limb impairments are often prescribed orthoses to preserve or enhance their mobility. Exploration of mobility experiences common among orthosis users may provide insights into how orthoses, and other mobility aids, are utilized and regarded. The objective of this study was to broadly explore how lower limb orthosis users describe their mobility. Materials and methods: Four focus groups were held online with participants who lived in the U.S. or Canada. Participants had at least six months of experience using an ankle-foot- and/or a knee-ankle-foot-orthosis for one or both legs. All discussions were transcribed and coded. Thematic analysis was used to identify cross-cutting themes. Results: Participants included 29 orthosis users with a variety of health conditions. Inter-related themes, including personal factors, situational contexts, and assistance were identified as elements that influenced participants' mobility. Participants described a process of modifying their mobility through the use and non-use of one or more mobility aids. Conclusions: The current study findings may assist clinicians in developing strategies to optimize orthosis users' mobility in different situations. Experiences described by participants in this study may also help researchers identify aspects of mobility most pertinent to orthosis users and inform the development of new outcome measures. Implications for Rehabilitation: People who use lower-limb orthoses share common mobility experiences, despite differences in health diagnoses. Orthosis users often have opportunities to modify their mobility by choosing to use or not use their brace(s) and/or handheld mobility aids. When providing mobility aid interventions, clinicians should consider how each patient's individual characteristics, including physical characteristics (e.g., the health condition and how it presents, pain, fatigue) and psychosocial characteristics (e.g., fear and confidence, self-motivation, emotional responses), can affect mobility. Clinicians may be able to help patients optimize their mobility by asking about environmental obstacles they regularly encounter and recommending strategies for utilization of mobility aids, including simultaneous use of multiple aids, use of one aid, or choosing not to use any aids, depending on the activity and situation. Clinicians should inquire about all mobility aids available to a patient at home and in the community, including fixed objects, and consider how new mobility aid interventions might affect the patient's mobility when used alone and in combination with other forms of assistance.